2023
DOI: 10.1021/acs.langmuir.2c03063
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Wetting and Free Fatty Acid Deposition on an Atomistic Hair Fiber Surface Model Incorporating Keratin-Associated Protein 5-1

Abstract: The complex development of cosmetic and medical formulations relies on an ever-growing accuracy of predictive models of hair surfaces. Hitherto, modeling efforts have focused on the description of 18-methyl eicosanoic acid (18-MEA), the primary fatty acid covalently attached to the hair surface, without explicit modeling of the protein layer. Herein, the molecular details of the outermost surface of the human hair fiber surface, also called the F-layer, were studied using molecular dynamics (MD) simulations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…85 This discrepancy between the experiments and simulations is likely a result of the simplified atomically-smooth surfaces used in the simulations. In reality, the underlying disordered protein layer 55 is likely to be rougher than the graphene layer used to represent it in the simulations. Despite this opposite trend, the RMS roughnesses for both model surfaces are quite close to the experimental values using a small scanning area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…85 This discrepancy between the experiments and simulations is likely a result of the simplified atomically-smooth surfaces used in the simulations. In reality, the underlying disordered protein layer 55 is likely to be rougher than the graphene layer used to represent it in the simulations. Despite this opposite trend, the RMS roughnesses for both model surfaces are quite close to the experimental values using a small scanning area.…”
Section: Methodsmentioning
confidence: 99%
“…54 MD simulations with atomistic resolution have also been used to study the adsorption of fatty acids onto the 18-MEA-covered ultrahigh sulfur proteins. 55…”
Section: Introductionmentioning
confidence: 99%
“…We have also discussed our findings with respect to existing studies reported in the literature. [28,29,35,36] 3.1 Organization and Structure of Fatty Acid Chains on KAP10-4…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] However, in realistic conditions the distribution of cysteine residues determines the spacing distance. For instance, the hair model based on the single segment KAP5-1 reported by Sanders et al achieved a lower surface density of 1.26 molecules nm À 2 for covalently bound 18-MEA compared to the optimal surface density (2.7-4.6 molecules nm À 2 ) identified from free energy analysis [28,35] and experiments reported mean surface coverage of approximately 2.2 molecules nm À 2 . [24] In our work with KAP10-4 support, the maximum possible surface density with BMEA is 1.05 molecules nm À 2 and to achieve the surface density of 2.2 molecules nm À 2 , a more realistic mixture of BMEA and FMEA were used.…”
Section: Damaged Hair Modelsmentioning
confidence: 98%
See 1 more Smart Citation